THE PROBLEM OF THE RIGHT OF IRREGULAR FLIGHTS - A. E. Rau; I. L. Danilevskaya (Научный вестник МГТУ ГА, 2016)
The article considers the problems of permit and notify regimes of airspace use of the Russian Federation on the basis of jurisprudence, and application of Art. 5 of the Chicago convention.